2016
DOI: 10.3892/ol.2016.4135
|View full text |Cite
|
Sign up to set email alerts
|

Initial evidence for Sec62 as a prognostic marker in advanced head and neck squamous cell carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is a malignancy with an increasing incidence. To aid with the selection of the most appropriate therapy, biomarkers have become a specific research focus. Sec62 is involved in endoplasmic reticulum stress tolerance and cell migration, and has been identified as a novel prognostic marker for non-small cell lung cancer. In addition, Sec62 may be a promising candidate in HNSCC. Pretreatment biopsies of 35 patients with locally advanced HNSCC, who were treated with def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 53 publications
6
45
1
3
Order By: Relevance
“…These data were strongly consistent with previous studies focused on the expression of SEC62 [27] and SOX2 [30, 35] in healthy and cancerous tissue of the head and neck region and consistently showed an overexpression of both genes in HNSCC tissue.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data were strongly consistent with previous studies focused on the expression of SEC62 [27] and SOX2 [30, 35] in healthy and cancerous tissue of the head and neck region and consistently showed an overexpression of both genes in HNSCC tissue.…”
Section: Discussionsupporting
confidence: 93%
“…For SEC62 , these data confirmed our previously reported findings for a smaller cohort of HNSCC patients, in which we analyzed SEC62 expression in tissue specimens of the primary tumor [27]. For SOX2 , some studies were consistent with our results and reported a better outcome of HNSCC patients with high SOX2 expression levels in the primary tumor [42, 48, 49].…”
Section: Discussionsupporting
confidence: 91%
“…Other protein substrates, including ERAD proteins, are degraded independently of SEC62 function. Moreover, SEC62 has been found to be upregulated in several types of cancer, where it is associated with increased metastatic and invasive potential, as well as higher ER stress tolerance (Greiner et al, 2011a,b;Wemmert et al, 2016). Whether SEC62's role in re-establishing basic ER physiology via degradation of UPR proteins is related to its role in tumorigenesis remains an area for further investigation.…”
Section: Er-phagy Receptorsmentioning
confidence: 99%
“…By contrast, it has a tumor-suppressive function in colon and breast cancer that is well established (Islam et al, 2017;Tang et al, 2007). SEC62 is also amplified in several cancers with a yet undefined molecular role (Hagerstrand et al, 2013;Wemmert et al, 2016). Because a well-established function of SEC62 is to resolve ER stress, it is important to emphasize that the UPR has a dual impact on tumors: it can support cancer cell growth, providing a machinery to deal with stress, but, on the other hand, it can have a cytotoxic effect and induce cell death via apoptosis.…”
Section: Er-phagy In Human Diseasesmentioning
confidence: 99%